Examining the level of service quality towards customer satisfaction at Melaka Stadium Corporation / Munira Mohd Yasin - Mohd Yasin, Munira (Faculty of Business and Management, 2007)
This research is conducted to examine the level of service quality towards customer satisfaction at Melaka Stadium Corporation. The attributes of service quality such as tangibility, reliability, responsiveness, assurance and empathy have been identified in order to investigate whether or not these factors have significant relationship with customer satisfaction. From this study, Melaka Stadium Corporation able to identify the problems which rely on the level customer satisfaction at Melaka Stadium Corporation, the level of service quality at Melaka Stadium Corporation and the relationship between customer satisfaction and service quality. Chapter one consist of introduction and background of the research, chapter two consist of literature review, chapter three research methodology and design, chapter four data analysis and interpretation of data and chapter five conclusion and recommendations.